GFG App
Open App
Browser
Continue

Class 8 RD Sharma Solutions – Chapter 8 Division Of Algebraic Expressions – Exercise 8.2

Question 1. Divide 6x3y2z2 by 3x2yz

Solution:

We can write 6x3y2z2 as 2 * 3 * x * x * x * y * y * z * z

We can write 3x2yz as 3 * x * x * y * z

Now ans = (6x3y2z2)/(3x2yz)

= (2 * 3 * x * x * x * y * y * z * z)/(3 * x * x * y * z)

= 2 * x * y * z

Question 2. Divide 15m2n3 by 5m2n2

Solution:

We can write 15m2n3 as 5 * 3 * m * m * n * n * n

We can write 5m2n2 as 5 * m * m * n * n

Now ans = (15m2n3)/(5m2n2)

= (3 * 5 * m * m * n * n * n)/(5 * m * m * n * n)

= 3 * n

Question 3. Divide 24a3b3 by -8ab

Solution:

We can write 24a3b3 as 3 * 8 * a * a * a * b * b * b

Now ans = (24a3b3)/(-8ab)

= -(3 * 8 * a * a * a * b * b * b)/(8 * a * b)

= -(3 * a * a * b * b)

= -3 * a * a * b * b

We can write -3 * a * a * b * b as -3 * a2 * b2

Question 4. Divide -21abc2 by 7abc

Solution:

We can write -21abc2 as -3 * 7 * a * b * c * c

We can write 7abc as 7 * a * b * c

Now ans = (-21abc2)/(7abc)

= -(7 * 3 * a * b * c * c)/(7 * a * b * c)

= -(3 * c)

= -3c

Question 5. Divide 72xyz2 by -9xz

Solution:

We can write 72xyz2 as 8 * 9 * x * y * z * z

Now ans = (72xyz2)/(-9xz)

= -(8 * 9 * x * y * z * z)/(9 * x * z)

= -(8 * y * z)

= -8yz

Question 6. Divide -72a4b5c8 by -9a2b2c3

Solution:

We can write -72a4b5c8 as -8*9*a*a*a*a*b*b*b*b*b*c*c*c*c*c*c*c*c

We can write -9a2b2c3 as -9*a*a*b*b*c*c*c

Now ans = (-72a4b5c8) /(-9a2b2c3)

= (8*9*a*a*a*a*b*b*b*b*b*c*c*c*c*c*c*c*c) / (9*a*a*b*b*c*c*c)

= (8*a*a*b*b*b*c*c*c*c*c)

= 8*a*a*b*b*b*c*c*c*c*c

We can write 8*a*a*b*b*b*c*c*c*c*c as 8 * a2 * b3 * c5

Question 7. Divide 16 * m3 * y2 by 4 * m2 * y

Solution:

We can write 16m3y2 as 4 * 4 * m * m * m * y * y

We can write 4m2y as 4 * m * m * y

Now ans = (16m3y2)/(4m2y)

= (4 * 4 * m * m * m * y * y)/(4 * m * m * y)

= (4 * m * y)

= 4my

Question 8. Divide 32 * m2 * n3 * p2 by 4 * m * n * p

Solution:

We can write 32m2n3p2 as 4 * 8 * m * m * n * n * n * p * p

Now ans = (32m2n3p2) / (4mnp)

= (4 * 8 * m * m * n * n * n * p * p) / (4 * m * n * p))

= (8 * m * n * n * p)

We can write 8 * m * n * n * p as 8 * m * n2 * p